Modification of Non Dairy Panna Cotta Using Coconut Milk and Soya Milk - Astuti, Ratih Dwi (Universitas Bunda Mulia, 2024)
Panna cotta is an italian dessert derived from based cream, milk, and gelatin.But it cannot be denied many people could not and choose not consume products for reasons of dairy milk allergies, lactose intolerance, restriction diet, and the potential health problems.The purpose of in this research to do a modification panna cotta and soy milk instead of cow milk, dairy cream and coconut milk instead of sweet corn has any the better for the body.What is the level fondness for the community in terms of taste, scent, color, texture, and display.The research is by this organoleptik deskritif quantitative, using kuisioner distributed to 41 respondents is east area of local communities. According to data collection results, the majority of the responders responded positively to the dessert.In terms of taste, as much as 56.1 % responders claim it's delicious and 43.9 % states it's delicious.Aromaically, 65.9 % responders express scent and 34.1 % very scented.In terms of texture, 46.1 % responders like soft texture and 46.3 % very soft.As much as 53.7 % responders love a very interesting color and 43.9 % likes an interesting color.Regarding physical appearances, 65.9 % responders judge very well and 34.1 % good.Related to a favorite level, 51.2 %s responders love this dish and 48.8 % very much like.This research result indicates that dessert non dairy panna cotta with a sauce of sweet corn pandanus consumers have the potential to be admitted.And our main bahan-bahan modification with a sauce of pandanus give variety to the feeling of, scent, and display, so that it may become attractive alternative for those who had a preference non dairy diet.However, further research can be done.